Analisis Produktivitas, Waktu, dan Biaya Alat Berat pada Pematangan Lahan Proyek Pondok Pesantren di Sukabumi - Septian Prakoso; Nia Kartika; Hartono Hartono (Jurnal Teknik Sipil, 2025)
Land clearing work is a crucial initial stage in a construction project, as it significantly affects both the schedule and project costs. This study aims to analyze the productivity, implementation time, and operational costs of heavy equipment—specifically excavators and bulldozers—on the Alkhaled Institute development project in Cikembar, Sukabumi. The methods used include field observation (time study), collection of primary and secondary data, and productivity calculations based on cycle time. The results show that the XCMG XE75DA excavator has a productivity rate of 46.91 m³/hour, while the Komatsu D31EX bulldozer reaches 134.74 m³/hour. The estimated duration of work is around 51 days for the excavator and 59 days for the bulldozer, with a total operational cost of Rp 480,196,000.00. This study provides recommendations for